Karakteristik Fisik dan Organoleptik Es Krim Susu Kedelai dengan Penambahan Kuning Telur Sebagai Penstabil - N.B, Agustia Zulfia; Hawa, Tidar Aden (KUBIS, 2023)
Soybeans are basically processed by the community into semi-finished foods, namely tempeh and tofu, and also into ready-to-eat foods such as soy milk. The people of Jember have a good interest in soy milk, as can be seen from the market share in Jember Regency which is quite good. MSME soy milk entrepreneurs located in Jember still produce it traditionally. Apart from that, the packaging and labeling used is still simple using plastic, so research into soy milk processing is needed to increase the added value of the product. One of the soy milk derivative products is ice cream. The aim of this research was to determine the overrun and melting power of soy milk ice cream and to determine the organoleptic properties of soy milk ice cream. Based on the results of organoleptic test calculations, the variable color, aroma, taste and texture that has a significant influence on the liking of soy milk ice cream is aroma because it has an F Hit value of 3.84 > F Tab 5% 3.19, which means it has an influence. The second most significant preference for soy milk ice cream is the flavor which has an F Hit value of 7.71 > F Tab 1% 5.08 and F Tab 5% 3.19. Which means it has a very real influence on the preference for soy milk ice cream.